'Crisis' and 'everyday' initiators: A qualitative study of coercion and agency in the context of methadone maintenance treatment initiation. (29th April 2016) - Damon, Will; Small, Will; Anderson, Solanna; Maher, Lisa; Wood, Evan; Kerr, Thomas; McNeil, Ryan
Abstract: Introduction and Aims: Patient attrition is common among people enrolled in methadone maintenance treatment (MMT) programs and most pronounced during the first year of treatment. However, the experiences of patients initiating MMT have been overlooked in the literature. This study explores experiences of MMT initiation among MMT patients, focusing on contextual influences on MMT initiation and perceptions of MMT and their subsequent influence on treatment retention. Design and Methods: Semi‐structured qualitative interviews were conducted with 39 MMT patients in Vancouver, Canada. Individuals reporting enrolment in MMT were recruited from within two ongoing cohort studies comprised of people who use drugs. Interview transcripts were analysed using an inductive and iterative approach. Results: Two groups of MMT initiators were identified: (i) 'crisis initiators' prescribed methadone following critical transition events, such as incarceration or pregnancy; and (ii) 'everyday initiators' enrolled in MMT as part of routine healthcare utilisation. While most 'crisis initiators' and some 'everyday initiators' described experiencing coercion during MMT initiation, 'crisis initiators' were further subjected to the coercive leveraging of their vulnerability to motivate 'consent' for MMT. 'Crisis initiators' developed negative views towards MMT and were more likely to discontinue treatment. Long‐standing patient–provider relationships and open dialogue were associated with more positive views regarding MMT, regardless of the circumstances of initiation. Discussion and Conclusion: Findings underscore the need for clear and effective communication regarding treatment regimens and expectations during MMT initiation. Furthermore, training in trauma‐informed care may help reduce perceptions of coercion and rates of early treatment termination. [Damon W, Small W, Anderson S, Maher L, Wood E, Kerr T, McNeil R. Crisis' and 'everyday' initiators: A qualitative study of coercion and agency in the context of methadone maintenance treatment initiation. Drug Alcohol Rev 2017;36:253–260]